2022
DOI: 10.3389/fimmu.2022.1016472
|View full text |Cite
|
Sign up to set email alerts
|

High levels of PF4, VEGF-A, and classical monocytes correlate with the platelets count and inflammation during active tuberculosis

Abstract: Platelets play a major role in coagulation and hemostasis; evidence supports the hypothesis that they also contribute to immunological processes. Increased platelet counts have been associated with poor prognosis in tuberculosis (TB). Platelet–monocyte aggregates have been reported in patients with TB, but it is still unclear if only one monocyte subpopulation is correlated to the platelet count; moreover, the platelet–monocyte axis has not been studied during latent tuberculosis (LTB). In this study, mononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In consonance with a previous report [ 21 ], the DS-TB group showed a higher platelet count than UC ( p < 0.0001) and LTB ( p < 0.0001). Similarly, DS-TB patients had a higher count of platelets than DR-TB patients ( p < 0.0004).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In consonance with a previous report [ 21 ], the DS-TB group showed a higher platelet count than UC ( p < 0.0001) and LTB ( p < 0.0001). Similarly, DS-TB patients had a higher count of platelets than DR-TB patients ( p < 0.0004).…”
Section: Resultssupporting
confidence: 92%
“…Regarding IL-4 levels, UC increased the level with TP stimulus [unstimulated: 2 (0.7-4); TP: 24 , p < 0.0151]. Interestingly, LTB increased IL-4 levels but under TL stimulus [0.7 (0.7-2); TL: 41 , p < 0.0106]; the DS-TB group was similar [unstimulated: 2 (0.7-3); TL: 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), p < 0.0461]. Regarding DR-TB, there were no observed changes (Figure 6D).…”
Section: Ltb Produces High Levels Of Il-10 and Il-4 In Response To Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our data, in A-TB patients, showed a significant increase in the number of platelets and monocytes in the non-cured group compared to the cured group, and, the increase in the number of monocytes in the non-cured group and the recovery of the cavity were positively correlated, consistent with reports, suggesting that our study is consistent with an immune mechanism of the platelet/monocyte axis. Although, the study showed no change in the frequency of classical and non-classical monocytes in DS-TB patients ( 35 ). Our data, in non-anemic TB patients, the number of platelets and monocytes did not change in the non-cured patients compared to the cured group, suggesting that monocytes are only a prognostic risk factor in A-TB patients and a key to our detailed analysis of A-TB monocytes.…”
Section: Discussionmentioning
confidence: 78%
“…Current research focusing on monocytes and their subsets in TB has found that CD16 monocyte is expanded in TB infection ( 33 ), while expansion of CD16 monocyte is reversed with anti-TB treatment ( 34 ). It was shown that DS-TB patients had an increased frequency of platelets and monocytes compared to LTB ( 35 ). Our data, in A-TB patients, showed a significant increase in the number of platelets and monocytes in the non-cured group compared to the cured group, and, the increase in the number of monocytes in the non-cured group and the recovery of the cavity were positively correlated, consistent with reports, suggesting that our study is consistent with an immune mechanism of the platelet/monocyte axis.…”
Section: Discussionmentioning
confidence: 99%